2004
DOI: 10.1046/j.1365-2796.2003.01293.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in blood pressure and body weight following smoking cessation in women

Abstract: Abstract. Janzon E, Hedblad B, Berglund G, Engström G (Malmö University Hospital, Malmö, Sweden). Changes in blood pressure and body weight following smoking cessation in women. Objective. Few have studied the long-term effects of smoking and smoking cessation on weight gain and blood pressure increase and compared with the age-related increases experienced by most adults. This study compared the development of weight and blood pressure in female never smokers, continuing smokers and smokers who quit smoking. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
53
1
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(66 citation statements)
references
References 21 publications
9
53
1
3
Order By: Relevance
“…In non-pregnant women, cessation of smoking has been associated with a higher risk of hypertension than continued smoking or never smoking, 43 a finding that appears to support our results. Further study is needed to confirm a similar association between cessation of smoking and gestational hypertension.…”
Section: Mediating Mechanismssupporting
confidence: 89%
“…In non-pregnant women, cessation of smoking has been associated with a higher risk of hypertension than continued smoking or never smoking, 43 a finding that appears to support our results. Further study is needed to confirm a similar association between cessation of smoking and gestational hypertension.…”
Section: Mediating Mechanismssupporting
confidence: 89%
“…A clinically important issue is that earlier literature reported that smoking cessation was associated with an increased incidence of hypertension. 50 In relation to this evidence, our decreasing trend of BP, partly explained by exercise effect, seems to be encouraging.…”
Section: Discussionsupporting
confidence: 54%
“…This finding is consistent with longitudinal results, in which BP levels were lower in smokers in comparison to nonsmokers and the incidence of hypertension tended to increase after the cessation of smoking. 21 However, the mechanism beyond the effect of smoking on BP is uncertain.…”
Section: Discussionmentioning
confidence: 99%